1987
DOI: 10.1029/ja092ia09p10029
|View full text |Cite
|
Sign up to set email alerts
|

Ion/ion and electron/ion cross‐field instabilities near the lower hybrid frequency

Abstract: Instabilities near the lower hybrid frequency are investigated by numerically solving the linear Vlasov electromagnetic dispersion equation. The configuration is that of two unmagnetized ion components, a less dense beam and a more dense core, streaming across a uniform magnetic field with magnetized electrons in the zero momentum frame. All three components are considered to have similar temperatures. This paper studies the parametric dependences of maximum growth rate for three distinct modes: the electron/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…almost perpendicular to the magnetic field. The occurrence of the MTSI-2 can change the picture obtained from 1-D simulations; however, the linear stability analysis by Gary et al (1987) has shown that the MTSI-2 is only dominant in the low electron beta case (β e < 0.5), while the present β e ∼ 1.7. We thus expect the MTSI-2 to be of minor importance.…”
Section: Linear Instability Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…almost perpendicular to the magnetic field. The occurrence of the MTSI-2 can change the picture obtained from 1-D simulations; however, the linear stability analysis by Gary et al (1987) has shown that the MTSI-2 is only dominant in the low electron beta case (β e < 0.5), while the present β e ∼ 1.7. We thus expect the MTSI-2 to be of minor importance.…”
Section: Linear Instability Analysismentioning
confidence: 86%
“…The waves with maximum growth of the MTSI-1 have wave vectors almost perpendicular to the magnetic field and can thus be observed in 1-D shock simulations. However, the waves with maximum growth of the MTSI-2 propagate oblique to the magnetic field (e.g., Gary et al, 1987) and will thus not be seen in 1-D simulations, which allow only for k vectors in the shock normal direction, i.e. almost perpendicular to the magnetic field.…”
Section: Linear Instability Analysismentioning
confidence: 99%
“…The same holds in the ramp region: instabilities with k vectors less oblique to the magnetic field may have larger growth rates and can modify the reformation process. In particular the modified two-stream instability between solar wind electrons and reflected ions with k vector components parallel to the magnetic field can occur in a multi-dimensional spatial system (Gary et al, 1987) and plays an important role in the foot region (Matsukiyo and Scholer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this region the cold magnetospheric ions and the crescent distribution of magnetosheath ions are distinct from each other. The relative drift between the two ion populations in the M direction perpendicular to B can excite the ion‐ion cross‐field instability, which produces lower hybrid‐like waves [ Papadopoulos et al , ; Gary et al , ]. The observed waves have phase velocities approximately between the two ion populations, consistent with an instability developing between the two ion populations producing the waves.…”
Section: Observationsmentioning
confidence: 99%